Hydrothermal alteration mineralogical footprints for New Zealand epithermal Au-Ag deposits. Issue 4 (2nd October 2019) - Simpson, Mark P.; Christie, Antony B.
ABSTRACT: Epithermal Au-Ag veins of the Hauraki goldfield are mostly hosted by volcanic rocks and are enclosed by extensive zones of hydrothermal alteration that are generally 6–50 km 2 in areal extent. The rocks are altered to a variety of hydrothermal minerals; the most common include quartz, adularia, illite, mixed-layered illite-smectite, chlorite, pyrite, calcite, albite and smectite. Some alteration minerals have zoned distributions. Widespread illite grades successively into overlying and bordering illite-smectite and outlying smectite. Significant quartz veins mainly occur in illite-altered rocks, but some can occur in illite-smectite altered rocks. Adularia commonly surrounds veins and can occur in rocks up to >500 m laterally from veins. Ammonium (NH4 ) minerals, when present, have a restricted distribution occurring laterally <100–300 m from veins. The significance of alteration minerals can be understood from a geothermal context where the system scale zonation of illite, illite-smectite and smectite outline the broad thermal structure of the former hydrothermal system, with illite formed in the hotter portion. Widespread adularia indicates zones of inferred high permeability and the upflow of boiling hydrothermal fluids. Most significant quartz veins occur in rocks altered to adularia and / or illite, restricting the target area, although both minerals can occur >500 m from veins. Where present, NH4 -minerals further restrict the target area.